Egypt. (c2018) - Nasreddine, Hala Nouhad (2018)
After deposing the Muslim Brotherhood-affiliated president, Mohamad Morsi, the Egyptian Supreme Council of the Armed Forces ensured the retrieval of power to the hands of the military. Consequently, ever since his inauguration in 2014 – and following the period of political turmoil and instability that stormed Egypt between 2011 and 2014 – the current president, Abdel Fattah El-Sisi, has been trying to resurrect the deep Nasserite state. This form of state – which is based on fear and suppression – is the only guarantee of the regime’s survival in the post-Arab Spring era. The thesis investigates the current manifestation of the deep state in some of the major constituents of the country: the armed forces and security personnel, the economy, the judiciary and the media. It further demonstrates the overlap between el-Sisi’s approach and that of Nasser, revealing a recurrent pattern – that involves both concrete provisions and rhetoric – associated with the deep state.